Kegiatan Edukasi Tahapan Pemberian Makanan Pendamping ASI Sebagai Upaya Penerapan Penyuluhan Kesehatan Rumah Sakit di Luar Gedung - Prasetyorini, Anif; Ramhawati, Indri; Shandy, Rafifah Nur; Ananta, Novian Saga; Cahyaningrum, Rina; Nafa R, Tria; Rahmawati, Indah (STIKES Yayasan RS.Dr.Soetomo, 2024)
Indonesian Nutritional Status Survey (SSGI), the prevalence of stunting has increased, partly due to less than optimal visits by toddlers to posyandu for measurements and weighing. Empowerment is the initial milestone in Hospital Health Promotion activities which can be implemented outside the building. The objectives to empower through education about the stages of giving complemengtary breast milk to mothers of toddlers. The Methods: outreach to the community around the hospital by providing pre-tests and post-tests to measure knowledge. The Results showed two approaches were used to carry out the activity: evaluation and presentation. The presentation and question-and-answer period is the first step. Four activities make up the presentation: the opening, introduction, implementation, and conclusion. The aim and objectives of the exercise are explained as part of the introductory activity. The explanation of the planned activities completes the introductory phase. Implementation efforts include giving participants information on what is meant by